Military Interventions As Omitted Variable Of Inversed Democratic Peace: An Empirical Evidence - Srđan Korać; Nenad Stekić (Srpska Politička Misao)
The paper examines the relationship between military interventions and democratisation processes which took place in targeted states. While many researchers try to identify relationship between the regime type and countries’ war proneness, the authors of this paper put these two variables in a reversed order. To test this so-called “inversed democratic peace” thesis based on an argument that an ongoing war is likely to lead to democratisation, we focus our analysis on the US interventions in Afghanistan, Iraq, Libya, and FR Yugoslavia (Kosovo). We deploy three variables: 1) Foreign policy similarity, to determine whether the intervening actor (USA) had similar or different foreign policy goals at the beginning of interventions; 2) Political regime similarity, to indicate whether there were any deviations in the quality of political regime between the intervening state and the target country, as indicated by the democratic peace postulates; 3) military interventions (independent variable). Foreign policy score includes S score dataset developed by Curtis S. Signorino and Jeffrey M. Ritter (1999), while for the political regime quality, the authors deploy Polity IV data. Statistical analysis including Pearsonʼs correlation, logistic regression and descriptive statistics, will be presented for specific dyad level in three specifically designated models. The authors conclude that it is more likely that military interventions affect further democratisation of the targeted post-conflict societies, if observed in a short term rather than in longitudinal domain, while the foreign policy similarity (with the United States) positively correlates in cases with more successful democratisation process.